2011
DOI: 10.1007/s11605-010-1197-8
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Therapy for Rectal Cancer: The Impact of Longer Interval Between Chemoradiation and Surgery

Abstract: An interval between chemoradiation and surgery ≥ 8 weeks is safe and is associated with a higher rate of pathologic complete response and decreased local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 25 publications
4
106
2
Order By: Relevance
“…Even though CRT has improved the outcome of rectal cancer, the optimal timing of surgical resection after CRT remains uncertain. De Campos-Lobato et al [1] showed that waiting for more than 8 weeks between completion of CRT and surgery was associated with significant improvement in pathological complete response (pCR) rate (30.8 vs. 16.5%, p = 0.03) and decreased the 3-year local recurrence rate (1.2 vs. 10.5%, p = 0.04). Other studies have indicated downstaging and better surgical outcomes with a delay of more than 8 weeks [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though CRT has improved the outcome of rectal cancer, the optimal timing of surgical resection after CRT remains uncertain. De Campos-Lobato et al [1] showed that waiting for more than 8 weeks between completion of CRT and surgery was associated with significant improvement in pathological complete response (pCR) rate (30.8 vs. 16.5%, p = 0.03) and decreased the 3-year local recurrence rate (1.2 vs. 10.5%, p = 0.04). Other studies have indicated downstaging and better surgical outcomes with a delay of more than 8 weeks [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemoradiotherapy (CRT) is considered the standard approach before any surgical intervention for locally advanced rectal tumors [1]. Total mesorectal excision combined with neoadjuvant CRT has resulted in significant improvement of local disease control, lower rates of local recurrence, more effective tumor downstaging, and greater success rates in sphincter-sparing surgery [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following completion of CRT, both individual series , population studies and a metaanalysis 3 all show that longer intervals up to a maximum of 12 -15 weeks appear associated with an increased chance of achieving a pCR at surgical resection, and counter-intuitively outcomes may also improve in terms of a significant reduction in 3-year local recurrence rate (1.2% vs. 10.5%, p = 0.04). 4 However, further extensions of this interval do not appear to benefit the patient. 5,6 Patients with rectal cancer, who achieve a pCR or near pCR, fare consistently better than the patients who fail to do so.…”
Section: For Debatementioning
confidence: 99%
“…1 He brings forth several key issues that remain among the top challenges in treating rectal cancer. We agree that it would obviously be paramount to identify which patients would achieve a pathologic complete response (pCR), but unfortunately this is not currently possible.…”
mentioning
confidence: 99%